2008
DOI: 10.1177/147323000803600209
|View full text |Cite
|
Sign up to set email alerts
|

Increased Expression of Paxillin is Found in Human Oesophageal Squamous Cell Carcinoma: A Tissue Microarray Study

Abstract: Oesophageal cancer is one of the most common cancers worldwide. Currently, the tumour, node, metastasis (TNM) staging system is the primary method for determining its extent and prognosis, however, data suggest this system does not predict prognosis accurately. Research has, therefore, concentrated on searching for specific biomarkers. Paxillin has been shown to play an important role in controlling cell spread and migration. Its over-expression is considered to correlate with the prognosis of some types of ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 10 publications
0
15
0
Order By: Relevance
“…And this is also true in the context of ESCCs, as a number of the identified differentially expressed genes involved in integrin signaling in this study (listed in Supplementary Table S4) have already been previously implicated in ESCC pathogenesis. These include CAV1, ROCK1, ITGB1, ICAM1, VCL, PXN, and SHC1 (36)(37)(38)(39)(40)(41)(42)(43)(44). Here, we report the identification and characterization of a tumor suppressor gene Rab25 in ESCCs, which was found to be significantly downregulated in the integrin signaling-associated pathway.…”
Section: Discussionmentioning
confidence: 91%
“…And this is also true in the context of ESCCs, as a number of the identified differentially expressed genes involved in integrin signaling in this study (listed in Supplementary Table S4) have already been previously implicated in ESCC pathogenesis. These include CAV1, ROCK1, ITGB1, ICAM1, VCL, PXN, and SHC1 (36)(37)(38)(39)(40)(41)(42)(43)(44). Here, we report the identification and characterization of a tumor suppressor gene Rab25 in ESCCs, which was found to be significantly downregulated in the integrin signaling-associated pathway.…”
Section: Discussionmentioning
confidence: 91%
“…The combined detection of FAK and paxillin may have more value in detecting tumor cells. Li et al (13) reported that in 100 samples of esophageal carcinoma, 27 exhibited high paxillin gene expression but only 6 samples of adjacent atypical hyperplasia exhibited paxillin expression. In addition, Chatzizacharias et al found that 54/91 cases of esophageal carcinoma had FAK overexpression, and its positive rate of expression was 59.3%.…”
Section: Discussionmentioning
confidence: 99%
“…It provides a platform for the integration and processing of adhesion and growth factor-related signals that are mainly involved in tumor metastasis and cell proliferation [32], [33]. Paxillin is overexpressed in many carcinomas, including bladder cancer [33], ESCC [34], [35], hepatocellular carcinoma (HCC) [36], NSCLC [37], salivary adenoid cystic carcinoma [38], and floor of mouth carcinoma [39].…”
Section: Introductionmentioning
confidence: 99%